Investigation of digital rupiah acceptance using UTAUT-3 model - Mau Bere, Alejandro Billyjoe; Putra, Richard Win; Wedari, Linda Kusumaning (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The adoption of central bank digital currencies (CBDC) has been popular in many countries, especially Indonesia which currently develops its own CBDC called digital rupiah, due to its potential benefits such as financial inclusion. Despite the potential benefits of digital rupiah, there is a lack of understanding regarding factors that affect digital rupiah user acceptance. This research aims to investigate the potential factor affecting the user acceptance of digital rupiah using the unified theory of acceptance and use of technology (UTAUT-3) model, incorporating awareness and privacy as additional variables. There are 218 respondents to this study from five provinces in Indonesia: Jakarta, West Java, East Java, Central Java, and Yogyakarta. The data were analyzed using the SEM-PLS method. The results of this study found that performance expectancy, effort expectancy, habit, personal innovativeness, and awareness are the significant factors that affect the behavioral intention of digital rupiah meanwhile facilitating condition, habit, personal innovativeness, and behavioral intention are the factors that significantly affect the use behavior of digital rupiah. This study identifies key factors influencing the user acceptance of the digital rupiah, providing valuable insights for stakeholders seeking to promote its adoption and use in Indonesia.